Sihler's whole mount nerve staining technique: a review - Mu, L (2010)
Sihler's stain is a whole mount nerve staining technique that renders other soft tissue translucent or transparent while staining the nerves. It permits mapping of entire nerve supply patterns of organs, skeletal muscles, mucosa, skin, and other structures after the specimens are fixed in neutralized formalin, macerated in potassium hydroxide, decalcified in acetic acid, stained in Ehrlich's hematoxylin, destained in acetic acid, and cleared in glycerin. The unique advantage of Sihler's stain over other anatomical methods is that all the nerves within the stained specimen can be visualized in their three-dimensional positions. To date, Sihler's stain is the best tool for demonstrating the precise intramuscular branching and distribution patterns of skeletal muscles, which are important not only for anatomists, but also for physiologists and clinicians. Advanced knowledge of the neural structures within mammalian skeletal muscles is critical for understanding muscle functions, performing electrophysiological experiments and developing novel neurosurgical techniques. In this review, Sihler's stain is described in detail and its use in nerve mapping is surveyed. Special emphasis is placed on staining procedures and troubleshooting, strengths and limitations, applications, major contributions to neuroscience, physiological and clinical significance, and areas for further technical improvement that deserve future research.